Publicness Between State and Market: The Struggle of Female Ojol Drivers Amid Intersectional and Sustainable Vulnerability - Setianingrum, Nurima; Nabil Falah, Afkaar; Margareta, Diah Pitaloka (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2026)
The digitalization of the public transportation sector has opened opportunities for many citizens, including women, to become ride-hailing motorcycle taxi (ojol) drivers, working flexibly as partners of a company without fixed contracts. This participation allows women to enter the public sphere through employment. However, women’s presence in the public sphere reveals multiple layers of precarity. Stemming from inadequate welfare and safety guarantees, exposure to harassment, and economic pressure under the partnership scheme for freelancers in the gig economy. This study focuses on the experiences and struggles of female ride-hailing motorcycle taxi drivers in the city of Yogyakarta as they face risks in the public sphere. It also seeks to understand the relationship between the state and corporations that shape their working conditions. This research also aims to answer two main questions. (1) How do female drivers confront multiple layers of precarity in both digital and physical publicness? (2) How are basic worker rights advocated by female ride-hailing drivers, and to what extent does this advocacy mitigate the vulnerabilities they face? These questions will be answered using qualitative methods, particularly through participatory observation and in-depth interviews. This study will contribute to the literature on women’s precarity in the freelance gig economy by highlighting the inequities in protective guarantees and public rights that should be ensured by the state. Its findings are expected to yield policy recommendations to improve protection and justice for female ride-hailing drivers as vulnerable workers in the public sphere.